School Financial Budgeting for Enhancing Educational Quality in Junior High Schools - Laras Ati; Widya Kusumaningsih; Qristin Violinda (Journal of Educational Sciences, 2026)
School financial budget management helps improve the quality of education through the effective utilization of resources. This study aims to describe the financial budgeting process in efforts to improve the quality of education at SMP Negeri 1 Pulosari. The novelty of this study lies in its focus on the identification and structured description of budgeting practices in educational financial management. The research employed a qualitative approach, utilizing interviews, observations, and documentation as data collection tools. The informants for this study were the school principal, the school committee, the school treasurer, the PPUr, and teachers. The research subjects were selected based on the location of the school under study. Data were analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results indicate that the budgeting process is conducted systematically through the identification of funding sources, the preparation of the RKAS, the determination of priorities, stakeholder engagement, and compliance with regulations. The identification of funding sources is carried out transparently and based on data. The use of the ARKAS application further supports transparency, accountability, effectiveness, and efficiency in financial management. Nevertheless, the budgeting process still faces challenges in the form of limited funds, policy changes, and high stakeholder expectations. The research findings highlight the importance of needs-based planning, strengthening stakeholder participation, and optimizing digital systems to support school financial management aimed at improving the quality of education.